2019
DOI: 10.1029/2018jd029896
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Environmental and Mesoscale Characteristics of Two Types of Mountain‐to‐Plain Precipitation Systems in the Beijing Region, China

Abstract: Beijing, China, is located in a region of complex terrain with high mountain ridges to the northwest and the Bohai Sea to the southeast. The origin of convective storms occurring on the plains can often be traced to the upstream mountains. Under weakly forced conditions, these convective storms most frequently evolve into squall lines (SL) and convective clusters (CC) when reaching the plains. In this study, we analyze 18 SL and 15 CC storm systems and assess their environmental and mesoscale differences betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 31 publications
1
20
0
Order By: Relevance
“…VDRAS is a four‐dimensional variational data assimilation system that can assimilate radar reflectivity and Doppler velocities from single or multiple radars into a simplified cloud model to yield an optimal solution to satisfy both the model physics and the radar observations simultaneously (X Chen, Zhao, et al, 2016; Z He et al, 2018; Sun & Crook, 1997, 2001; Sun & Zhang, 2008; Sun et al, 2010; Xiao et al, 2019). It has been successfully implemented in the United States, China, Australia, and so forth, for analyses and short‐term forecasts of convective systems including SLs (e.g., Sun & Zhang, 2008; Z He et al, 2018) and supercells (e.g., Sun, 2005).…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…VDRAS is a four‐dimensional variational data assimilation system that can assimilate radar reflectivity and Doppler velocities from single or multiple radars into a simplified cloud model to yield an optimal solution to satisfy both the model physics and the radar observations simultaneously (X Chen, Zhao, et al, 2016; Z He et al, 2018; Sun & Crook, 1997, 2001; Sun & Zhang, 2008; Sun et al, 2010; Xiao et al, 2019). It has been successfully implemented in the United States, China, Australia, and so forth, for analyses and short‐term forecasts of convective systems including SLs (e.g., Sun & Zhang, 2008; Z He et al, 2018) and supercells (e.g., Sun, 2005).…”
Section: Methodology and Datamentioning
confidence: 99%
“…In addition, the sampling density and coverage of low‐level radar observations decrease as the distance from a radar increases. By assimilating surface observations, VDRAS can deduce the low‐level kinematic and thermodynamic structures, as well as the prominent features of these convective systems (e.g., X Chen, Zhao, et al, 2016; Sun & Zhang, 2008; Sun et al, 2010; Xiao et al, 2019). Similar results are confirmed in this case (not shown).…”
Section: Methodology and Datamentioning
confidence: 99%
“…For example, the characteristics of weakly forced mountain‐to‐plain precipitation systems were analysed based on radar observations and high‐resolution reanalysis data produced by VDRAS (Xiao et al ., 2017). Using storm‐scale reanalysis data produced by VDRAS, distinct features of the squall lines and convective clusters storms are revealed in terms of their convective environments and mesoscale structures, such as cold pool, horizontal wind convergence, and humidity distribution (Xiao et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the mechanism analysis, X. Xiao, et al. (2019) and Wu et al. (2020) investigated different data assimilation strategies for the initialization of convective‐scale numerical models and found that the assimilation of near‐surface temperature and the geostationary satellite data could improve forecasting skills for this event.…”
Section: Introductionmentioning
confidence: 99%